O processo de elaboração de princípios orientadores para a construção do projeto político-pedagógico - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This research aimed to understand the methodological process used for the collective construction of political-pedagogical projects used by the management teams of elementary schools in the municipal network of Dom Pedrito - RS. Since it was carried out in my workplace, the methodology used to reach the objective was action research. The theoretical framework covered Democratic Management and the Political-Pedagogical Project, with emphasis on the contributions of Veiga (2004 and 2013), Libâneo (2015), Padilha (2017) and Medel (2012). For data collection, two meetings were held for the diagnosis and three meetings to perform the action, where representatives of the management teams of nine elementary schools of the municipal network participated, in which we discussed the main difficulties and challenges faced by schools in an attempt to collectively build their political-pedagogical projects. From the data collected through the meetings, the following categories of analysis emerged: collective construction of the PPP, subdivided into concept of collective construction of the PPP and challenges to the collective construction of the PPP; participation and involvement of the school community, subdivided into participation of parents or guardians, student participation and teacher participation; challenges of participation; teachers do not discuss the PPP in class; productive and efficient meetings. In view of the above, it was possible to reaffirm that the greatest difficulty that the management teams encounter is to achieve an effective participation of all segments in the construction/reconstruction of the document, because the way they participate, without many not expressing their opinion, does not configure an effective collective construction, does not define the identity of the school nor its intentionality. There is still a long way to go for the collective construction of a political-pedagogical project in schools, and it is necessary that the participants receive the necessary conditions for its implementation, through the implementation of training and especially the availability of a satisfactory amount of time for this purpose, through the implementation of law number 2.634/2022 by the Secretary of Education.
Keywords: Construção Coletiva; Participação; Projeto Político-Pedagógico; Collective Construction; Participation; Political-Pedagogical Project; CNPQ::CIENCIAS HUMANAS